2013
DOI: 10.3109/02699206.2013.823242
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic complexity and stuttering in Arabic

Abstract: The current study investigated whether phonetic complexity affected stuttering rate in Jordanian Arabic speakers. Speakers were assigned to three age groups (6-11, 12-17 and 18+ years). An Arabic index of phonetic complexity (AIPC) was developed. Each word was given a score based on the number of complex phonetic properties out of a total of nine that it contained in the AIPC. The results showed that stuttering on function words for Jordanian Arabic did not correlate significantly with the AIPC score for any a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As previously noted, results from the studies that have employed the IPC indicate that phonetic complexity is associated with stuttered words in older children and adults but similar findings of significance have not been reported in children (Al-Tamimi et al, 2013: 6–11 years of age; Dworzynski & Howell, 2004: beyond 6 years of age; Howell et al, 2006: 11–18 years of age; Howell & Au-Yeung, 2007: beyond 6 years of age). Given that the IPC is based on infant–toddler speech development patterns, these findings are surprising as the fluent speech of younger speakers should presumably be more vulnerable to phonetic difficulty than older speakers.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…As previously noted, results from the studies that have employed the IPC indicate that phonetic complexity is associated with stuttered words in older children and adults but similar findings of significance have not been reported in children (Al-Tamimi et al, 2013: 6–11 years of age; Dworzynski & Howell, 2004: beyond 6 years of age; Howell et al, 2006: 11–18 years of age; Howell & Au-Yeung, 2007: beyond 6 years of age). Given that the IPC is based on infant–toddler speech development patterns, these findings are surprising as the fluent speech of younger speakers should presumably be more vulnerable to phonetic difficulty than older speakers.…”
Section: Introductionmentioning
confidence: 55%
“…However, as proposed by Buhr and Zebrowski (2009), data support the notion that moments of stuttering during early development – particularly at the utterance-initial position – appear to be more closely associated with planning utterance-level factors, such as utterance length, as opposed to word-level factors, such as grammatical class or phonetic complexity. Future studies are required to examine the role of these same utterance- and word-level factors over time, and at ages that more closely match the cohorts for which phonetic complexity (and grammatical classification) have been linked to overt moments of stuttering (e.g., Al-Timimi et al, 2013; Dworzynski & Howell, 2004; Howell & Au-Yeung, 2007; Howell et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work on EXPLAN has investigated Spanish (Howell & Au-Yeung, 2007), Japanese (Smith & Howell, 2013), Persian (Vahab, Zandiyan, Falahi & Howell, 2013) and Arabic (Al-Tamimi, Khamaiseh & Howell, 2013). The properties of Cs and Fs in these languages differ markedly from English.…”
Section: Introductionmentioning
confidence: 99%
“…Howell & Dworzynski, 2005). Research has demonstrated a relationship for older children and adults who stutter (e.g., Al-Timimi, Khamaiseh, & Howell, 2013; Dworzynski & Howell, 2004; Howell & Au-Yeung, 2007; Howell et al, 2006) but not younger children who stutter (e.g., Coalson & Byrd, 2016; Coalson et al, 2012; Dworzynski & Howell, 2004; Howell & Au-Yeung, 1995; Logan & Conture, 1997; Throneburg et al, 1994). Bernstein Ratner (2005) has suggested that past findings of phonetic complexity as a significant contributor to stuttered speech, in the manner predicted by the EXPLAN model, is difficult to determine due to a number of confounding methodological and theoretical concerns.…”
Section: Introductionmentioning
confidence: 99%